Form and Meaning of Verb Reduplication in Devayan Language of Simeulue Aceh - Mulyani, Restria; Deliana, Deliana; Nasution, Khairina (Budapest International Research and Critics University, 2021)
This research aims to describe the form and meaning of verb reduplication in Devayan language of Simeulue Aceh. One of the regional languages in Aceh Indonesia. The research uses descriptive qualitative research method. The data source is done by written and oral data. The data is written from the folklore (Nafi-Nafi), the words of advice in Nandong, and devayan dictionary. While the oral data source from the original speaker with the collection technique Data used listen and talk method and then analyze the data with the method of Padan(distributional method) and Agih(Identity method) continued with the technique of reading the script. The result of the research finds that the form of the verb reduplication in devayan language of Simeulue Aceh are : 1)Basic verb reduplication (2). Affixed verb reduplication. The affixed verb reduplication consist of: (1) Verb reduplication prefixed (Ma-, Mampa-, Mansi,and ni-) and (2) Infixed Reduplication(-um). The meaning of contained in verb reduplication Devayan language of Simeulue aceh are: (1) Repetition meaning 2) Mutual or reciprocal meaning (3). Meaning of done without purpose. 4). meaning about thing (5) Meaning of similarity in time (6) Meaning of done carelessly 7) Meaning of intensity, (8) Meaning of issuing and producing and (9) meaning of doing and giving.